Melanocytic nevi and tattooing. - Milano, A. (European Journal of Pediatric Dermatology, 2019)
There does not seem to be a greater risk of melanoma on tattooed skin due to the disproportion between the number of tattooed and cases of melanomas on tattoo, which are thirty so far in the literature, mostly set on blue or black (2). Tattoo professionals know that when you tattoo, you must stay at a distance of 1 cm from nevi, and not stop at their immediate periphery, given their possible expansion (1). Nevertheless it still happens today to observe tattoos on nevi linked to the presence of improvised tattooists and inexperienced clients. It is not right to tattoo on melanocytic nevi, especially because their clinical monitoring and the intraoperative differential diagnosis between metastatic lymph nodes and lymph nodes incorporating dark pigments become more difficult. These rules should be even more stringent in the population at risk of melanoma which should be previously informed by doctors, even general practitioners.